Wideband Low Noise Oscillator suitable for Injection Locking - Monteiro, Ruben Emanuel Estrela (2019)
There is a growing need to design compact and low power transceiver circuits. The increasingly crowded frequency spectrum leads to increased challenges associated with transceiver design. In particular, it becomes imperative that the oscillator circuits have a low phase noise. RC oscillators have the ability to produce wideband oscillations with reduced area and low power consumption. However, a serious drawback is its high phase noise, which leads to poor circuit performance. To improve the performance of an RC oscillator, it is common for it to be integrated into a frequency synthesizer. The most common approach of a synthesizer is the Phase- Locked Loop (PLL). This approach leads to an increase in the area and complexity of the circuit. Another approach to a synthesizer is an Injection-Locked Oscillator (ILO), which achieves similar performances to a PLL without the disadvantages referred to above. In this thesis, an ILO based on an RC oscillator, using a Spin Torque Oscillator (STO) as a reference generator, is presented. The circuit is implemented in two different Complementary Metal-Oxide-Semiconductor (CMOS) technologies: 130 nm CMOS and 180 nm CMOS. The STO used as reference has characteristics similar to a nanometric device developed at the International Iberian Nanotechnology Laboratory (INL). In addition, the ILO operates in a wide frequency band ranging from 100 MHz to 3 GHz, has a power consumption ranging from 2.94 mW to 6.81 mW for 130 nm CMOS technology, whereas in 180nm CMOS technology it consumes between 4.86 mW and 13.96 mW. Thus, the work developed in the course of this thesis serves as proof of concept for the manufacture of a fully integrated hybrid ILO using the STO technology in conjunction with CMOS circuits.